Lean Service Approach for Consulting Services Company - Kusrini, Elisa; Nisa, Fathia; Helia, Vembri Noor (International Journal of Integrated Engineering, 2019)
The service industry sector is one of the livelihoods in Indonesia. This sector has increased from year to year. This study aims to identify and determine the amount of dominant waste in consulting service companies based on the concept of lean service and provide recommendations to minimize the occurrence of dominant waste from the causal factors. The results of the identification of waste using the value stream mapping show that there are activities that are non-value-added with a total time of 200.52 minutes of a total time of 839.01 minutes or 23.90% in the process of public training services. Based on the future state from value stream mapping after processed improvements there was founded that the time of activities that non-value-added reduced by 136.36 minutes, from 839.01 minutes to 702.65 minutes or reduced by 16.25%. The proposed improvements provided based on the analysis of critical waste causes to minimize waste dominant in the form of waste waiting are the addition of new employees for marketing, making Standard Operating Procedure, setting training price standards, and increasing bandwidth to increase internet speed in the work environment.